Исследование явления запаздывания зажигания высоковольтного тлеющего разряда для повышения рабочего давления газоразрядных электронных пушек - Тутык, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The results of studies of the time of retardation tr of the ignition of a high-voltage glow discharge on the operation of low-vacuum gas-discharge electronic guns (LGEG) with a hollow anode in the pulse mode are given. It is shown that the time tr consists of the statistical time of retardation ts and the time of formation tf . Dependences of the time tr on various parameters are found. The method of using the time of retardation to increase the working pressure of LGEG by a diminution of the steepness of their volt-ampere characteristics S = ΔI/ΔU is offered and experimentally confirmed at the high-voltage pulse length tp < tr.